2. Упрости выражение и найди его значение: а) -3 (2х - 1 ) - (-7х + 4 ) +5 (- х - 3) при х= -2 б) -4 (-0,8х + 2у) - (4,2х - у) при х= 2, у = -1

2. Упрости выражение и найди его значение: а) -3 (2х - 1 ) - (-7х + 4 ) +5 (- х - 3) при х= -2 б) -4 (-0,8х + 2у) - (4,2х - у) при х= 2, у = -1
Гость
Ответ(ы) на вопрос:
Гость
а) - 3 * (2х - 1) - (-7х + 4) + 5 * (-х - 3) = - 6х + 3 + 7х - 4 - 5х - 15 = (-6х + 7х - 5х) + (3 - 4 - 15) = - 4х - 16 при х = - 2 - 4 * (-2) - 16 = 8 - 16 = - 8 б) - 4 * (-0,8х + 2у) - (4,2х - у) = 3,2х - 8у - 4,2х + у = (3,2х - 4,2х) + (у - 8у) = - х - 7у при х = 2, у = - 1 - 2 - 7 * (-1) = - 2 - (-7) = - 2 + 7 = 5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы